Consumer behaviour and branding : concepts, readings and cases : the Indian context - Ramesh Kumar, S. (Pearson Power : Dorling Kindersley (India), 2009)
India is one of the emerging markets that pose a unique set of challenges to marketers. The importance of the context and the usefulness of concepts in the Indian context is the core proposition of Consumer Behaviour and Branding: Concepts, Readings and Cases-The Indian Context. The diversity of a mix of factors such as cultural aspects, lifestyles, demographics and unbranded offerings make consumer behaviour a fascinating study, and this book focuses on the behavioural principles of marketing and its application to branding in the Indian context.